1987
DOI: 10.1002/macp.1987.021881021
|View full text |Cite
|
Sign up to set email alerts
|

Monte‐Carlo‐simulation for the structure of copolymer molecules of chemical inhomogeneity of second type

Abstract: A method is discussed for Monte-Carlo-simulation of copolymer molecules with chemical inhomogeneity of the second type. The copolymer molecules are formed by a polyreadon with monomer addition without chain termination, e.g. in case of an anionic ''living" polymerization. The reliability of the method was statistically tested with examples. The method allows a clear presentation of the copolymer molecules mentioned in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In other cases these probabilities exhibit a clear dependence on i. 29 Within the framework of the approach discussed, it can be rigorously shown that the value of the probability P R (i) for the products of anionic copolymerization exactly coincides with the component X R of the vector of instantaneous composition of a copolymer formed by the free-radical mechanism, pro-vided the value of conversion is p ) i/l m . By way of illustration Figure 1c presents the theoretical dependence P 1 (i) for copolymers of styrene and butadiene prepared by the anionic polymerization technique at values of reactivity ratios r 1 ) 0.004, r 2 ) 12.9 found earlier 25 for this system.…”
Section: Quantitative Theory Of "Living" Copolymerizationmentioning
confidence: 90%
See 2 more Smart Citations
“…In other cases these probabilities exhibit a clear dependence on i. 29 Within the framework of the approach discussed, it can be rigorously shown that the value of the probability P R (i) for the products of anionic copolymerization exactly coincides with the component X R of the vector of instantaneous composition of a copolymer formed by the free-radical mechanism, pro-vided the value of conversion is p ) i/l m . By way of illustration Figure 1c presents the theoretical dependence P 1 (i) for copolymers of styrene and butadiene prepared by the anionic polymerization technique at values of reactivity ratios r 1 ) 0.004, r 2 ) 12.9 found earlier 25 for this system.…”
Section: Quantitative Theory Of "Living" Copolymerizationmentioning
confidence: 90%
“…The Monte Carlo simulation method was employed for determining probabilities P 1 (i) to find a monomeric unit M h 1 at the ith position from the beginning of a growing polymer chain. 29 A similar problem has been addressed by means of computer simulation using the cooperative motion algorithm, 30 the application of which allowed one to predict thermodynamic as well as other properties of gradient copolymers. Particularly, the dependence of the static collective structure factor on the wave vector was explored for a number of systems representing copolymers with various distributions of monomeric units along the chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical model was found to be inconvenient for the modeling of the present system. As may be easily seen, the relative reactivity ratios rij enter into the analytical model (eqs [18][19][20][21][22] as reciprocal values, making the model very sensitive to small rij. Since this is the case for several r^i n the present calculations and estimation errors are especially high for small rtj values (see results of the TM method), results obtained by means of this model are not reliable.…”
Section: [Complex] = [M2mj + [M2s1]mentioning
confidence: 99%
“…ref. [1][2][3][4][5][6][7][8] and older papers cited there. Most often it was used to "normal" radical copolymerization, i.e.…”
Section: Introductionmentioning
confidence: 99%